Can advanced endoscopic techniques for assessment of mucosal inflammation and healing approximate histology in inflammatory bowel disease?. (July 2019) - Nardone, Olga Maria; Cannatelli, Rosanna; Zardo, Davide; Ghosh, Subrata; Marietta, Iacucci
The targets of therapy in inflammatory bowel disease have transformed in the last few years. The standard definition of mucosal healing assessed using white light standard definition endoscopy is being challenged because even when endoscopy suggests mucosal healing, the presence of histological activity can often still be observed. Of note, microscopic signs of inflammation correlate with clinical outcomes such as risk of relapse, hospitalization and colorectal cancer. Therefore, histological healing has increasingly become an important target to achieve. Advanced endoscopic technologies have been developed and many are starting to be adopted in daily clinical practice. They can provide a more detailed view of the mucosal and vascular architecture almost at the histology level, including crypt, vessel architecture and cellular infiltration. So, these can provide a more accurate definition of mucosal and histological healing. In this review we focus on new advanced endoscopic techniques, and how these have the potential to reduce the gap between histological and mucosal healing.